2015
DOI: 10.1111/1471-0307.12243
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the microstructural and textural properties of Lighvan cheese produced from bovine milk fortified with protein and gum tragacanth during ripening

Abstract: The effect of 0.02% gum tragacanth, sodium caseinate or milk protein concentrate (MPC70) on the physiochemical, microstructural and textural properties of Lighvan cheese produced from bovine milk was investigated. The microstructure of cheese samples was studied by scanning electron microscopy (SEM), and the SEM micrographs were analysed using 3D images, surface plots and binarised SEM images. The texture parameters of bovine Lighvan cheese containing sodium caseinate were similar to those of ovine Lighvan che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…As can be seen, incorporation of Zedu gum into the LFC matrix could result in the openness of cheese microstructure, and this would be related to the occupation of spaces by moisture. This is in agreement with the findings of Aminifar and Emam‐Djome (), who reported that large holes in cheese containing 0.02% gum tragacanth could be associated with the water binding capacity of the gum. After 60 days of ripening, the SEM images (Figure ) revealed a more homogeneous microstructure in AS 0.25 in comparison with the day 1 of ripening.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As can be seen, incorporation of Zedu gum into the LFC matrix could result in the openness of cheese microstructure, and this would be related to the occupation of spaces by moisture. This is in agreement with the findings of Aminifar and Emam‐Djome (), who reported that large holes in cheese containing 0.02% gum tragacanth could be associated with the water binding capacity of the gum. After 60 days of ripening, the SEM images (Figure ) revealed a more homogeneous microstructure in AS 0.25 in comparison with the day 1 of ripening.…”
Section: Resultssupporting
confidence: 93%
“…As can be seen, incorporation of Zedu gum into the LFC matrix could result in the openness of cheese microstructure, and this would be related to the occupation of spaces by moisture. This is in agreement with the findings of Aminifar and Emam-Djome (2015), who 0.05). Control full-fat cheese (FFC), control low-fat cheese without Zedu gum (CLFC), low-fat cheese with 0.1 g of gum/kg of milk (AS 0.1) and low fat with 0.25 g of gum/kg of milk (AS 0.25).…”
Section: Microstructuresupporting
confidence: 94%
“…With the fat reduction, the texture was tighter, although the addition of basil seed and xanthan gum caused moisture to entrap within the cheese was increased and created a softer texture (Sharafi et al, 2019 ). In the previous studies, the authors reported that various fat replacers such as xanthan, novel, galactomannan, basil, and WPC80 decreased cheese harness, similar to our finding (Aminifar et al, 2014 ; Rashidi et al, 2015 ; Ribas et al, 2019 ; Sharafi et al, 2019 ). Contrary to our results, Hosseini‐Parvar et al ( 2015 ) found that an increment in the level of basil seed gum resulted in more hardness in processed cheese (Hosseini‐Parvar et al, 2015 ).…”
Section: Resultssupporting
confidence: 91%
“…Textural profile analysis allowed evaluating the physical properties of cheese, which are commonly able to differentiate between many cheese varieties, and are considered by the consumer as determinants of overall quality and preference [44]. The differences usually observed in textural properties of ripened cheese could be totally attributed to variations in the moisture content; the water is in fact able to act in dairy products as a plasticizer, inducing a liquid-like behavior [45].…”
Section: Discussionmentioning
confidence: 99%